Dr. Eric Seidlitz: Valuable Lessons from the Unconventional - Makar, Ameir; Syed, Wasimuddin (The Meducator, 2014)
Dr. Eric Seidlitz is a Researcher in the department of Pathology & Molecular Medicine at McMaster University. He has a diverse background, with a B.Sc in Zoology/Botany, a B.A. (first class Honours) degree in Physiological Psychology, a M.Sc. degree in Psychology/Electrophysiology, and a Ph.D. in Physiology and Pharmacology. After working for 8 years at the Sick Children Hospital in Toronto, he joined the Singh Lab at the Cancer Centre in Hamilton in 1998, where he started his research in bone metastasis. Aside from his research, he currently teaches the first year Cellular & Molecular Biology course in the Bachelor of Health Sciences program, alongside Dr. PK Rangachari.